Effect of tamoxifen in patients with thin endometrium who underwent frozen–thawed embryo transfer cycles: a retrospective study - Ji, Mengxia; Fu, Xiaohua; Huang, Danni; Wu, Ruifang; Jiang, Yunqing; Huang, Qiongxiao (Frontiers in Endocrinology, 2023)
Introduction Thin endometrium leads to an impaired implantation rate. The aim of the study is to compare the clinical outcomes of tamoxifen (TAM) and hormone replacement therapy (HRT) used in patients with thin endometrium (<7mm) in frozen-thawed embryo transfer (FET)cycles. Methods A total of 176 FET cycles with thin endometrium were retrospectively analyzed in our center from Jan 2020 to May 2022. According to patients' own will, 112 patients were allocated to the HRT group and 64 patients chose the TAM protocol. Clinical outcomes were compared between two groups. Result The duration of treatment was shorter in the TAM group(12.03±2.34d) than the HRT group (16.07±2.52 d), which was statistically different (p<0.05). The endometrial thickness on the transfer day of the TAM group (7.32±1.28 mm) was significantly thicker than that of the HRT group (6.85±0.89mm, p<0.05). The clinical pregnancy rate of the TAM group (50.0%) was higher than that of the HRT group (36.6%), but there was no significant difference (p >0.05). The early miscarriage rate was significantly lower in the TAM group compared with the HRT group (5.9% Vs 26.8%, adjusted OR 0.10, p<0.05), while the live birth rate was higher in the TAM group (46.9% Vs 26.8%, adjusted OR 2.24, p<0.05) compared with the HRT group. Conclusion For patients with thin endometrium, TAM effectively improved the endometrial thickness and increased the live birth rate. TAM can be used as an alternative protocol for patients with thin endometrium.